Rho GTPase-dependent plasticity of dendritic spines in the adult brain - Martino, Assunta; Ettorre, Michele; Musilli, Marco; Lorenzetto, Erika; Buffelli, Mario; Diana, Giovanni (Frontiers in Cellular Neuroscience, 2013)
Brain activity is associated with structural changes in the neural connections. However, in vivo imaging of the outer cortical layers has shown that dendritic spines, on which most excitatory synapses insist, are predominantly stable in adulthood. Changes in dendritic spines are governed by small GTPases of the Rho family through modulation of the actin cytoskeleton. Yet, while there are abundant data about this functional effect of Rho GTPases in vitro, there is little evidence that Rho GTPase signaling in the brain is associated with changes in neuronal morphology. In the present work, both chronic in vivo two-photon imaging and Golgi staining reveal that the activation of Rho GTPases in the adult mouse brain is associated with little change of dendritic spines in the apical dendrites of primary visual cortex pyramidal neurons. On the contrary, considerable increase in spine density is observed i) in the basal dendrites of the same neurons ii) in both basal and apical dendrites of the hippocampal CA1 pyramidal cells. Moreover, functional analysis shows increase in basal glutamatergic neurotrasmission and activity-dependent plasticity only in CA1 neurons. While confirming that Rho-GTPase dependent increase in spine density can be substantial, the study indicates region and dendrite selectivity with relative stability of superficial cortical circuits.